(untitled) (Materiali di Estetica. Terza serie, 2016)
This article focuses on the criticism that Guido Davide Neri has continuously addressed to realism in its double aspect of an epistemological paradigm and of the political project of “realization”. In this text the latter of two aspects is chosen as a departure point of inquiry, as it allows to follow Neri’s argumentation from the discovery of concrete socio-political contradictions in “really existing socialism”, proposed in Aporie della realizzazione (1980), towards the analysis of its theoretical premises. It is maintained that the main target of such analysis is the particular interpretation of Marx’s “11th thesis on Feuerbach”, according to which the philosophy, as a mere theory, had to be abandoned in favor of scientific and political practice. The article thus aims to discuss Neri’s critical interrogation of Marxist theory also in Prassi e conoscenza (1966), his early major work, and in the late essay Marx: prassi e natura (1999). Furthermore, it is argued that Neri’s philosophical itinerary is substantially continuous: if, on the one hand, the theoretical basis for the future critique of political realization is already implicit in Neri’s early confrontation with dogmatic understanding of theory-praxis relation, characteristic of certain readings of Marx, on the other hand, the critique of such readings does not preclude Neri from critical reevaluation of Marx’s own writings, just as it is revealed by the late essay. The article closes expressing conviction in the actuality of Neri’s critical project even in today’s philosophical, political and ecological context.